Nosocomial Isolates and Their Drug Resistant Pattern in ICU Patients at National Institute of Neurological and Allied Sciences, Nepal - Pashupati Bhandari; Ganesh Thapa; Bharat Mani Pokhrel; Dwij Raj Bhatta; Upendra Devkota (International Journal of Microbiology)
Multidrug resistant organisms are increasing day by day and the cause is poorly known. This study was carried out from June 2011 to May 2012 at National Institute of Neurological and Allied Sciences Kathmandu, Nepal, with a view to determining drug resistant pathogens along with detection of extended spectrum β-lactamase (ESBL), AmpC β-lactamase (ABL), and metallo-β-lactamase (MBL) producing bacteria causing infection to ICU patients. A standard methodology was used to achieve these objectives as per recommendation of American Society for Microbiology. ESBL was detected by combined disc assay using cefotaxime and cefotaxime clavulanic acid, ABL by inhibitor based method using cefoxitin and phenylboronic acid, and MBL by imipenem-EDTA combined disk method. Two hundred and ninety-four different clinical samples such as tracheal aspirates, urine, pus, swabs, catheter tips, and blood were processed during the study. Most common bacteria were Acinetobacter spp. Of the total 58 Acinetobacter spp., 46 (79%) were MDR, and 27% were positive for ABL and 12% were for MBL. Of the 32 cases of Staphylococcus aureus, 18 (56%) were MDR. Findings of this study warrant routine β-lactamase testing in clinical isolates.